Microglia Activation in the Brain as Inflammatory Biomarker of Alzheimer's Disease Neuropathology and Clinical Dementia. Issue 1 (9th June 2013) - Xiang, Zhongmin; Haroutunian, Vahram; Ho, Lap; Purohit, Dushant; Pasinetti, Giulio Maria
Abstract : The role of microglia-mediated inflammation in the progression of Alzheimer's disease (AD) neuropathology remains unclear. In this study, postmortem brain sections from AD and control cases were subjected to Human Leukocyte Antigen (HLA)-DR immunohistochemistry to examine microglia activation in the progression of AD assessed by pre-mortem clinical dementia rating (CDR) and postmortem pathological manifestations of neuritic plaque (NP) and neurofibrillary tangle (NT) according to the Consortium to Establish a Registry for Alzheimer's Disease (CERAD). In both gray and white matter of the entorhinal cortex (EC) and HLA-DR immunostaining increased with the progression of CDR or CERAD NP, and to a lesser degree with CERAD NT. Between CDR stages HLA-DR significance was found in moderate (CDR 2) to severe dementia (CDR 5) where as between CERAD NP stages staining increased significantly from NP 0 (no plaque) to NP 1 (sparse plaques), suggesting increased microglia activation begins with amyloid NP deposition. In the hippocampus, a significant increase in microglia immunostaining was found in the pyramidal cell layer of CA1 as early as CDR 1, and in the upper molecular layer of the dentate gyrus in CDR 0.5. This increase continues with the progression of CDR and reaches maximum in CDR 5. When assessed by CERAD NP stages however, a significant increase in microglia immunostaining was found only in mid-to-late stages (NP 3) and reduced staining was seen in NP 5. These results suggest that microglia activation increases with the progression of AD, with the increase varying depending on the involved brain region.